2001
DOI: 10.1002/1097-0142(20010701)92:1<126::aid-cncr1300>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival in patients with compensated cirrhosis and small hepatocellular carcinoma after percutaneous ethanol injection therapy

Abstract: A “reorientation” of the concept of total synthesis of natural products emphasizes a biology‐inspired, chemistry‐driven approach without compromising the sanctity of basic research and the noble objectives of co‐worker training in an academic setting. Structure‐based organic synthesis provides a unique framework to capitalize on data gleaned from the bioactivity of natural products in conjunction with X‐ray crystallography, molecular modeling, and NMR spectroscopy for the design and synthesis of new drug proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 109 publications
4
37
0
Order By: Relevance
“…As mentioned earlier, the other factor was a platelet count of <100 Â 10 9 /L. Thrombocytopenia, indicating advanced liver cancer, has been reported to be a poor prognostic factor of curative treatments, such as resection (29), radiofrequency ablation (30), and percutaneous ethanol injection therapy (31). Besides the HCC itself, hepatic failure is another major cause of death among HCC patients.…”
Section: Discussionmentioning
confidence: 92%
“…As mentioned earlier, the other factor was a platelet count of <100 Â 10 9 /L. Thrombocytopenia, indicating advanced liver cancer, has been reported to be a poor prognostic factor of curative treatments, such as resection (29), radiofrequency ablation (30), and percutaneous ethanol injection therapy (31). Besides the HCC itself, hepatic failure is another major cause of death among HCC patients.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that thrombocytopenia is a poor prognostic factor of achieving curative treatment, such as resection, 38 radiofrequency ablation, 39 and percutaneous ethanol injection, 40 although there are differing opinions. 41 However, 19 detected tumors (76%) measured 5 cm in the current study and were detected early enough to allow the patients receive curative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Pompili et al evaluated the therapeutic efficacy of PEI for patients with Child-Pugh class A and tumors > 5 cm in diameter, and reported that alpha-fetoprotein level and liver function were factors which contributed to survival [21] . Ebara et al evaluated the therapeutic efficacy of PEI for patients with ≤ 3 lesions of small HCC, and found that alpha-fetoprotein level and liver function were factors contributed to the suvival [22] .…”
Section: Discussionmentioning
confidence: 99%